The development of novel organocatalysts for asymmetric methylene transfer in the Corey-Chaykovsky reaction - Kavanagh, Sarah (Trinity College (Dublin, Ireland). School of Chemistry, 2012)
To date, the enantioselective preparation of terminal three-membered heterocycles via the Corey-Chaykovsky (CC) reaction has been characterised by unsatisfactory enantioselectivities. In the benchmark literature report involving asymmetric methylene transfer to benzaldehyde, the terminal epoxide product was afforded in 57% ee, while in the benchmark literature report involving asymmetric methylene transfer to an imine, the terminal aziridine product was formed in just 19% ee. Both of these procedures require the use of (superjstoichiometric quantities (one or two equivalents respectively) of chiral sulfide.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.